If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + 3) + y = 2(y + 4) + -4 Reorder the terms: 4(3 + y) + y = 2(y + 4) + -4 (3 * 4 + y * 4) + y = 2(y + 4) + -4 (12 + 4y) + y = 2(y + 4) + -4 Combine like terms: 4y + y = 5y 12 + 5y = 2(y + 4) + -4 Reorder the terms: 12 + 5y = 2(4 + y) + -4 12 + 5y = (4 * 2 + y * 2) + -4 12 + 5y = (8 + 2y) + -4 Reorder the terms: 12 + 5y = 8 + -4 + 2y Combine like terms: 8 + -4 = 4 12 + 5y = 4 + 2y Solving 12 + 5y = 4 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 12 + 5y + -2y = 4 + 2y + -2y Combine like terms: 5y + -2y = 3y 12 + 3y = 4 + 2y + -2y Combine like terms: 2y + -2y = 0 12 + 3y = 4 + 0 12 + 3y = 4 Add '-12' to each side of the equation. 12 + -12 + 3y = 4 + -12 Combine like terms: 12 + -12 = 0 0 + 3y = 4 + -12 3y = 4 + -12 Combine like terms: 4 + -12 = -8 3y = -8 Divide each side by '3'. y = -2.666666667 Simplifying y = -2.666666667
| 5.4x+3.4=14.2 | | 2x^2+5x^4-12x^3=0 | | 2x-3/9+x+1/2=x-4 | | -24+6x=8(3x+6) | | -b+1.8=5.3 | | 4x-5/3-7x=2/1 | | -5(t-3)+7t=4t-2 | | 10p+9+11=-2(2p+4)-3(2p-2) | | (x+3)2-4=0 | | 6n+12=78 | | -7=-7.5z-(-7z+3) | | log[4](2x-9)-log[4](x-8)=3 | | 3(x+9)=6x | | 2=x-4(2x+3) | | 8(r+2)=54 | | 7x=12x-45 | | (+15)+(-7)+(+1)= | | y=57-2 | | 2x+4x=3x+3 | | 3(x-9)=6x | | 1/5y=9-2/5y | | 4c-6=-2 | | 2n+5+4=-1 | | 4C-6=two | | xb=ya | | 2x=11+x | | 6x+1=6(x+1) | | Y=0.15x+0.55 | | 5(15+x)=-70 | | 2*5+8/2=18 | | 2.49+x= | | 9x+1/3x=0 |